2013
DOI: 10.1161/circgenetics.113.000288
|View full text |Cite
|
Sign up to set email alerts
|

Compound and Digenic Heterozygosity Predicts Lifetime Arrhythmic Outcome and Sudden Cardiac Death in Desmosomal Gene–Related Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Background-Mutations in genes encoding for desmosomal proteins are the most common cause of arrhythmogenic right ventricular cardiomyopathy (ARVC). We assessed the value of genotype for prediction of lifetime major arrhythmic events and sudden cardiac death (SCD) in desmosomal gene-related ARVC. Methods and Results-The overall study population included 134 desmosomal gene mutation carriers (68 men; median age 36 years ) from 44 consecutive ARVC families undergoing comprehensive genetic screening. The probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
146
2
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 227 publications
(164 citation statements)
references
References 44 publications
7
146
2
9
Order By: Relevance
“…Our results are also consistent with the results of prior studies that have reported that men are at higher arrhythmia risk than women 17, 19, 22, 23. Finally, our results are also consistent with prior studies that have reported that T‐wave inversions on precordial leads of the ECG13, 15, 20 and a PVC count of ≥1000 on 24‐hour Holter15 are predictors of appropriate ICD therapy for VT/VF.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also consistent with the results of prior studies that have reported that men are at higher arrhythmia risk than women 17, 19, 22, 23. Finally, our results are also consistent with prior studies that have reported that T‐wave inversions on precordial leads of the ECG13, 15, 20 and a PVC count of ≥1000 on 24‐hour Holter15 are predictors of appropriate ICD therapy for VT/VF.…”
Section: Discussionsupporting
confidence: 92%
“…6) [59]. Comprehensive exonic sequence analysis of the known desmosomal AC-related genes currently identifies approximately 50 % of AC probands [60][61][62][63]. The most commonly defective AC gene is PKP2 (10-45 %), followed by DSP (10-15 %), DSG2 (7-10 %) and DSC2, JUP (1-2 %).…”
Section: Ac Genes/mutations and Diagnostic Implicationsmentioning
confidence: 99%
“…The inheritance pattern of AC is more complex than previously appreciated, with frequent requirement for more than one 'hit' for fully penetrant disease [60,61,66,67]. The low penetrance of AC may be explained by a "recessive-like" inheritance pattern, based on the fact that AC probands often carry homozygous or compound heterozygous variants in the same gene, or digenic/oligogenic variants in a cluster of desmosomal genes.…”
Section: Ac Genes/mutations and Diagnostic Implicationsmentioning
confidence: 99%
“…Это связано с тем, что экспрессивность и пенетрантность заболева-ния очень вариабельны даже у членов одной семьи -носителей мутации. Кроме того, по всей видимости, значительную роль в формировании фенотипа играют различные факторы, такие как пол (мужской пол явля-ется дополнительным фактором риска ВСС [18,19]), возраст, уровень физических нагрузок, сопутствующие инфекционные заболевания, гормональный фон, эмо-циональный стресс [20].…”
Section: материал и методыunclassified
“…В 2009г Bhuiyan, et al описали дигенные формы АКПЖ, вызванные мутациями в генах DSC2 и DSG2 [21]. Дальнейшие исследования подтвердили, что множественные мутации в генах десмосом ассоциированы с более тяжелым течением заболевания и являются дополнительным фактором риска ВСС, выявление которого, в сочетании с дру-гими факторами, расширяет показания к импланта-ции ИКД [19]. Описано, что у имеющих мутации в гене десмоплакина достоверно чаще развивается систолическая дисфункция ЛЖ (40%) и ХСН (13%), нежели у лиц с мутацией в гене плакофилина [22].…”
Section: материал и методыunclassified